(untitled) (Bangladesh Journal of Medical Physics, 2017)
During thyroid scan with Technetium-99m (Tc-99m) Pertechneate, the maximum uptake is supposed to occur after 15 to 20 minutes of intravenous administration for normal healthy persons. The purpose of this study is to determine the time of maximum uptake of Technhetium Pertechneate by measuring counts over the thyroid gland during thyroid scan and to correlate the time of maximum uptake with thyroid functions measured biochemically. The number of patients studied was 136 of which 113 were females and 23 were males with the age range between 7 to 70 years. Among all, about 46% cases showed maximum count in the interval of 10-25 minutes. Though 38.2% of patients showed maximum uptake of tracer after 25 minutes, the count rate did not increase significantly after this time which justifies the conventional time of thyroid scanning. In general, the time of maximum uptake was earlier in females than males. Percentage of patients with hyperthyroidism is almost same for both males and females (13% and 12% respectively) but for females occurrence of hypothyroidism is higher than males (26% vs 17%). The total uptake of Tc-99m Pertechnetate for hyperthyroidism patients in each interval is greater than that of euthyroid patients but the time of maximum uptake is random for both males and females without any correlation with thyroid function. Bangladesh Journal of Medical Physics Vol.8 No.1 2015 1-6